Development of Digital Learning Media Integrated with Augmented Reality in Learning Fiction Texts in Elementary Schools - Alfa, Dyah Nuhia; Astuti, Tri (LPPM Universitas Pendidikan Mandalika, 2025)
This research aims to develop a digital learning media integrated with augmented reality on the material of intrinsic elements of fictional texts in fourth-grade elementary school. This research applied the Research and Development method by adopting the ADDIE model which has five stages; analysis, design, development, implementation, and evaluation. The subjects of this research were media experts, material experts, class teachers, and fourth-grade elementary school students. Data analysis was used with initial and final data analysis. The Shapiro-Wilk formula was used as a precondition test for the normality test in the initial data analysis. The final data analysis used the T-Test and N-Gain test using SPSS 26 software. The results showed that augmented reality-based digital learning media received very feasible qualifications from experts in the field of media and materials. Digital learning media integrated with augmented reality is also considered very practical seen from student responses and teacher responses. The results of the T- Test and the N- Gain test both in the small group trial and the large group trial showed a significant difference in results with moderate criteria before and after using augmented reality-based digital learning media. Therefore, digital learning media integrated with augmented reality has been proven to improve student learning outcomes. Digital learning media integrated with augmented reality is feasible, practical, and effective to utilize in Indonesian language subject material of intrinsic elements of fiction text in fourth-grade elementary school.